CRISPR/Cas9-Induced fad2 and rod1 Mutations Stacked With fae1 Confer High Oleic Acid Seed Oil in Pennycress (Thlaspi arvense L.) - Jarvis, Brice A.; Romsdahl, Trevor B.; McGinn, Michaela G.; Nazarenus, Tara J.; Cahoon, Edgar B.; Chapman, Kent D.; Sedbrook, John C. (Frontiers in Plant Science, 2021)
Pennycress (Thlaspi arvense L.) is being domesticated as an oilseed cash cover crop to be grown in the off-season throughout temperate regions of the world. With its diploid genome and ease of directed mutagenesis using molecular approaches, pennycress seed oil composition can be rapidly tailored for a plethora of food, feed, oleochemical and fuel uses. Here we utilized Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 technology to produce knockout mutations in the FATTY ACID DESATURASE2 (FAD2) and REDUCED OLEATE DESATURATION1 (ROD1) genes to increase oleic acid content. High oleic acid (18:1) oil is valued for its oxidative stability that is superior to the polyunsaturated fatty acids (PUFAs) linoleic (18:2) and linolenic (18:3), and better cold flow properties than the very long chain fatty acid (VLCFA) erucic (22:1). When combined with a FATTY ACID ELONGATION1 (fae1) knockout mutation, fad2 fae1 and rod1 fae1 double mutants produced ~90% and ~60% oleic acid in seed oil, respectively, with PUFAs in fad2 fae1 as well as fad2 single mutants reduced to less than 5%. MALDI-MS spatial imaging analyses of phosphatidylcholine (PC) and triacylglycerol (TAG) molecular species in wild-type pennycress embryo sections from mature seeds revealed that erucic acid is highly enriched in cotyledons which serve as storage organs, suggestive of a role in providing energy for the germinating seedling. In contrast, PUFA-containing TAGs are enriched in the embryonic axis, which may be utilized for cellular membrane expansion during seed germination and seedling emergence. Under standard growth chamber conditions, rod1 fae1 plants grew like wild type whereas fad2 single and fad2 fae1 double mutant plants exhibited delayed growth and overall reduced heights and seed yields, suggesting that reducing PUFAs below a threshold in pennycress had negative physiological effects. Taken together, our results suggest that combinatorial knockout of ROD1 and FAE1 may be a viable route to commercially increase oleic acid content in pennycress seed oil whereas mutations in FAD2 will likely require at least partial function to avoid fitness trade-offs.